Prevalence and trajectories of post-COVID-19 neurological manifestations: a systematic review and meta-analysis - Giussani, Giorgia; Westenberg, Erica; Garcia-Azorin, David; Bianchi, Elisa; Yusof Khan, Abdul Hanif Khan; Allegri, Ricardo Francisco; Atalar, Arife Cimen; Baykan, Betul; Crivelli, Lucia; Fornari, Arianna; Frontera, Jennifer A.; Guekht, Alla; et al. (S. Karger AG, 2024)
Introduction: The aim of this systematic review and meta-analysis was to evaluate the prevalence of thirteen neurological manifestations in people affected by COVID-19 during the acute phase and at 3, 6, 9 and 12-month follow-up time points. Methods: The study protocol was registered with PROSPERO (CRD42022325505). MEDLINE (PubMed), Embase, and the Cochrane Library were used as information sources. Eligible studies included original articles of cohort studies, case-control studies, cross-sectional studies, and case series with ≥5 subjects that reported the prevalence and type of neurological manifestations, with a minimum follow-up of 3 months after the acute phase of COVID-19 disease. Two independent reviewers screened studies from January 1, 2020, to June 16, 2022. The following manifestations were assessed: neuromuscular disorders, encephalopathy/altered mental status/delirium, movement disorders, dysautonomia, cerebrovascular disorders, cognitive impairment/dementia, sleep disorders, seizures, syncope/transient loss of consciousness, fatigue, gait disturbances, anosmia/hyposmia, and headache. The pooled prevalence and their 95% confidence intervals were calculated at the six pre-specified times. Results: 126 of 6,565 screened studies fulfilled the eligibility criteria, accounting for 1,542,300 subjects with COVID-19 disease. Of these, four studies only reported data on neurological conditions other than the 13 selected. The neurological disorders with the highest pooled prevalence estimates (per 100 subjects) during the acute phase of COVID-19 were anosmia/hyposmia, fatigue, headache, encephalopathy, cognitive impairment, and cerebrovascular disease. At 3-month follow-up, the pooled prevalence of fatigue, cognitive impairment, and sleep disorders was still 20% and higher. At six- and 9-month follow-up, there was a tendency for fatigue, cognitive impairment, sleep disorders, anosmia/hyposmia, and headache to further increase in prevalence. At 12-month follow-up, prevalence estimates decreased but remained high for some disorders, such as fatigue and anosmia/hyposmia. Other neurological disorders had a more fluctuating occurrence. Discussion: Neurological manifestations were prevalent during the acute phase of COVID-19 and over the 1-year follow-up period, with the highest overall prevalence estimates for fatigue, cognitive impairment, sleep disorders, anosmia/hyposmia, and headache. There was a downward trend over time, suggesting that neurological manifestations in the early post-COVID-19 phase may be long-lasting but not permanent. However, especially for the 12-month follow-up time point, more robust data are needed to confirm this trend.